High performance networking, computing, and communication systems second international conference, ICHCC 2011, Singapore, May 5-6, 2011. selected papers - ICHCC 2011 (2011 Singapore); Wu, Yanwen; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book constitutes the refereed post-proceedings of the Second International Conference on Theoretical and Mathematical Foundations of Computer Science, ICTMF 2011, held in Singapore in May 2011. The conference was held together with the Second International Conference on High Performance Networking, Computing, and Communication systems, ICHCC 2011, which proceedings are published in CCIS 163.The 84 revised selected papers presented were carefully reviewed and selected for inclusion in the book. The topics covered range from computational science, engineering and technology to digital signal processing, and computational biology to game theory, and other related topics.
Electronic reproduction.
Keywords: High performance computing -- Congresses; Electronic books